Perlindungan Data Pribadi dalam E-Commerce Syariah: Studi Komparatif Indonesia dan Singapura: Personal Data Protection in Sharia E-Commerce: Comparative Study of Indonesia and Singapore - Rudysta Dihyah Al-Kalabi; Muhibban (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2025)
The development of Islamic e-commerce has had a significant impact on the transaction patterns of modern society, especially in Indonesia and Singapore. However, this progress also raises major challenges in terms of personal data protection, which becomes a crucial issue in maintaining consumer trust and maintaining compliance with sharia principles. This study aims to analyze and compare the regulation and implementation of personal data protection in sharia e-commerce in both countries. A qualitative approach is used through literature study and analysis of legal documents, such as the Personal Data Protection Act (PDP) in Indonesia and the Personal Data Protection Act (PDPA) in Singapore. The results show that Singapore has a more mature legal framework with strong enforcement mechanisms, while Indonesia still faces challenges in implementation and public education. However, both countries strive to harmonize regulations with sharia principles, such as maintaining trustworthiness and fairness. This study provides recommendations for the development of more effective and sharia-compliant personal data protection policies, so as to increase consumer confidence in the sharia e-commerce sector.